Muhammadiyah, Sufism, and the quest for ‘authentic’ Islamic spirituality - Ahmad Muttaqin; Ustadi Hamsah; Robby Habiba Abror (Indonesian Journal of Islam and Muslim Societies, 2023)
This current paper explores and analyzes the trend of Sufism discourses and practices among Indonesian Muslim modernist-reformer organizations with special reference to the Muhammadiyah movement. The public tends to categorize Muhammadiyah as an anti-Sufism movement. A close study, however, shows that the existence of Sufism discourse and practices is a clear religious phenomenon among its individual figures and members, although organizationally Muhammadiyah does not recognize the existence of Sufi orders (tarekat). Based on the data collected from subjective-ethnographic notes of the organization’s programs and activities as well as literature studies of the organization documents, this study implements Stephen Katz’s philosophical model. It shows that Muhammadiyah is searching for Islamic spirituality by promoting the authenticity of tasawuf aspects, namely tauh}id or monotheism and akhlaq al-karimah or noble characters as reflected in the concept of ih}san. In this regard, Sufism is defined as a system of values and spirituality, not involved in a particular Sufi order. Muhammadiyah interprets Sufism as ethical values and ethos to do virtuous actions in society.